Cooperative work in virtual higher education - Guevara Ingelmo, Raquel María (2021)
Cooperative work presents multiple benefits in the teaching-learning process of students of any age. In higher education, and more specifically in the training of teachers and future teachers, it is also considered of special relevance since it favors in the student the development of the personal, social and professional skills necessary to carry out their work in the school environment, an environment in which cooperation is the main organizing tool. This paper presents the experience of incorporating cooperative work in a virtual subject of the postgraduate Secondary Education Teacher Training. A total of 135 students participated in the research (67.5% female; 32.5% male), the mean age being 35.1 years (DT: 7.9). Through a survey, the students valued this work methodology very positively, stating, the majority, having improved or achieved some of the main benefits that this method provides: greater motivation for the task, better final result, the development of critical thinking and have improved their personal relationship skills. The results obtained are discussed and some conclusions are detailed for the development of this type of initiatives in online teaching.